EVALUATING THE TEACHING PERFORMANCE FOR THE STAFF MEMBERS IN PHYSICAL EDUCATION COLLEGE FROM THE PERSPECTIVE OF STUDENTS - Mohammad, Pro.Dr. Ahmed Qasem; Hassan, Sabri Sulaiman (Journal of Duhok University, 2019)
The study aimed to identify the level of teaching performance of staff members in college of Physical Education at the University of Duhok, and to identify the significance of differences in the teaching performance of college members according to the variables of age, sex, grade and academic background (scientific - theoretic). The sample of the study included (140) male and female students selected by random stratified sample among the students of the college of Physical Education at the University of Duhok. The study was based on a questionnaire consisting of (34) paragraphs distributed over four areas (preparation and planning of the lesson, scientific research, measurement and evaluation, dialogue and discussion with students), and each paragraph has five alternatives to answer, after checking its psychometric properties. Data were processed using Pearson correlation coefficient, T-test of two independent samples, and mono-variance analysis. In conclusion, the results showed that the level of teaching performance of college staff members in general was moderate, and the results revealed that there are significant differences in the point of view for students on the teaching performance of college staff members due to the gender variable. The results did not show any significant differences in teaching performance from the students’ point of view due to age, grade and background variables. According to the results, a set of recommendations and proposals were presented.